2017
DOI: 10.1007/s00280-017-3447-x
|View full text |Cite
|
Sign up to set email alerts
|

A physiologically based pharmacokinetic and pharmacodynamic (PBPK/PD) model of the histone deacetylase (HDAC) inhibitor vorinostat for pediatric and adult patients and its application for dose specification

Abstract: Purpose: This study aimed at recommending pediatric dosages of the histone deacetylase (HDAC) inhibitor vorinostat and potentially more effective adult dosing regimens than the approved standard dosing regimen of 400 mg/day, using a comprehensive physiologically-based pharmacokinetic/pharmacodynamic (PBPK/PD) modeling approach. Methods: A PBPK/PD model for vorinostat was developed for predictions in adults and children. It includes the maturation of relevant metabolizing enzymes. The PBPK model was expanded … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 72 publications
1
6
0
Order By: Relevance
“…The P‐PBPK dose prediction articles included in the study, the name of the drug, the platform, and the study's funding are described in Table 1. Verified PBPK models of drugs are presented in support of pediatric dose prediction (Figure 4): 13 articles reported results from P‐PBPK models, which are presented in support of dose selection, 30–42 five articles were on the optimization of dosage in the design of future pediatric clinical studies, 3,29,43–45 and six articles reported findings from studies on determining dose regimens 46–51 . Fourteen publications were on some special pediatric populations and uncommon diseases with an assessment of renal impairment, 52–56 children with obesity, 57–60 and pediatric patients with severe coronavirus disease 2019 (COVID‐19) disease 61–65 .…”
Section: Resultsmentioning
confidence: 99%
“…The P‐PBPK dose prediction articles included in the study, the name of the drug, the platform, and the study's funding are described in Table 1. Verified PBPK models of drugs are presented in support of pediatric dose prediction (Figure 4): 13 articles reported results from P‐PBPK models, which are presented in support of dose selection, 30–42 five articles were on the optimization of dosage in the design of future pediatric clinical studies, 3,29,43–45 and six articles reported findings from studies on determining dose regimens 46–51 . Fourteen publications were on some special pediatric populations and uncommon diseases with an assessment of renal impairment, 52–56 children with obesity, 57–60 and pediatric patients with severe coronavirus disease 2019 (COVID‐19) disease 61–65 .…”
Section: Resultsmentioning
confidence: 99%
“…Secondly, phenoconversion for some conditions (e.g., inflammation) may only develop after prolonged or repeated exposure, which requires in-vitro models, such as 3D liver spheroids, in which the long-term consequences of these factors for drug metabolism can be adequately studied [ 68 , 69 ]. In-silico models, such as physiologically based pharmacokinetic (PBPK) models, have also been suggested as an excellent approach to study phenoconversion [ 70 , 71 , 72 , 73 , 74 , 75 ]. These models are particularly suitable to investigate the effects of complex interactions between multiple drugs and disease states.…”
Section: Discussionmentioning
confidence: 99%
“…These models have been used frequently to simulate drug pharmacokinetics [ 13 15 ] and especially in elucidating complex DDI with various co-medications, all of which may be impossible to study through dedicated clinical trials [ 16 18 ]. PBPK models are often linked with PD models in order to predict changes in drug effect due to extrinsic or intrinsic factors that affect the drug PK, for which a recent example being the work of Moj et al [ 19 ]. Blei [ 20 ] developed a PBPK model for amlodipine, but the model did not include CYP3A4-mediated clearance, which is essential in order to model mechanistic DDI with perpetrator drugs.…”
Section: Introductionmentioning
confidence: 99%